Bioassessment Of River Ganga In Uttarakhand Stretch (India) Using Benthic Macro-Invertebrates As Bioindicator (Applied Biological Research, 2019)
The sedentary lives of macro-invertebrates enable them to act as continuous  monitor of water quality of freshwater bodies. Some specific families of  benthic macro-invertebrate fauna belonging particularly to the Order  Ephemeroptera, Trichoptera, Plecoptera, Hemiptera, Coleoptera, Diptera,  Molllusca, Crustacea, Odonata, Hirudinea, Oligochaeta, Polychaeta and  Planaria have been recognized as bioindicator of water quality by Biological  Monitoring Working Party (BMWP). The present study was carried out to  explore the taxonomic richness of macro-zoobenthos found in various habitats  and biological water quality of river Ganga in Uttarakhand stretch of India at  3 locations viz., Haridwar barrage, Jagjeetpur sewage treatment plant (STP)  upstream and downstream. The samples were collected twice a year to  elucidate seasonal variation in taxa occurrence. A total of 1,560 individuals  belonging to 32 families and 12 taxonomic orders were recorded. Biological  water quality at Haridwar barrage was found to be clean in both the seasons.  Direct discharge of untreated sewage from Jagjeetpur STP had profound  effect on the biota of river and lead to community replacement at downstream  of discharge. Dominant Ephemeroptera colonies were replaced by Diptera  family Chironomidae at this location and thereby showed decline in biological  water quality.
Keywords: Bioindicators; biological water quality; benthic macro invertebrates; saprobity; taxonomic richness